Adipositas & Bewegung / Obesity & Physical Activity - Vuori I (Dynamic Media Sales Verlag, 2016)
There is great need to increase health-enhancing physical activity in most populations. At individual and group level, guidance provided by health professionals can be effective. The primary health care system (PHCS) is in principle a favorable channel to provide physical activity (PA) counseling, but in reality this service is offered to onlya small proportion of the clients. Many barriers for PA counseling can be listed, but most of them are consequences of the root cause, low priority of the counseling. The primary cause for this is, in turn, low confidence in the usefulness, especially effectiveness, of PA counseling. In order to increase confidence in PA counseling,firm evidence ofits effectiveness to sufficiently and sustainably increase PAto lead to the expected health outcomes has to be provided. Furthermore, counseling should be shown to be effective in real world conditions, and effective counseling procedures should be documented in detailedand standardized ways in order to make them analyzable and reproducible. These requirements are hard to meet. Currently, there are only two evidence-based recommendations on PA counseling endorsed by an independent expert panel. Thus, more and new kindsof research and development has to be done in order to improve the effectiveness, feasibility, and cost- and competitive effectiveness of PA counseling in order to get it accepted large-scale and permanently in the routine functions of the PHCS.KEY WORDS: Physical Activity, Counseling, Primary Health Care, Evidence-Based Recommendations